Preparation of carbon/transition metal dichalcogenide hybrids for water-related applications - Chen, Bo (2016)
Carbon-based three-dimensional (3D) architectures have received extensive research interest in the last few decades. Recently, it was found that the properties of carbon-based materials can be greatly tuned by surface modification with other materials (such as transition metal dichalcogenides (TMDs)) or tuning of its internal structures. To address multiple problems in modification of carbon-based materials, this thesis has been organized into separate chapters according to the material used and the technique developed. Particular attentions are made to elaborate the following points in their respective chapters: how to synthesize novel carbon-based 3D architectures from biomass; how to coat ultrathin two-dimensional (2D) TMDs on the surface of 3D carbon; how to assemble of 2D nanosheets to 3D hybrid heterostructures via one-pot reaction; how to prepare flexible carbon/TMD hybrid fibers with good mechanical properties; how to use powerful techniques to characterize the as-obtained novel carbon/TMD hybrid materials; demonstrating the potential of these hybrid materials for water-related applications like water remediation and water-splitting.